Influence of water evaporation/absorption on the stability of glycerol–water marbles. Issue 59 (28th October 2019) - Lin, Xinxing; Ma, Wei; Chen, Lihui; Huang, Liulian; Wu, Hui; Takahara, Atsushi
Abstract : The influence of water evaporation and absorption on the stability of aqueous glycerol marbles was investigated. Abstract : The porous shell structure of liquid marbles allows liquid vapor to enter in/out of the liquid marbles, leading to the deformation/collapse of liquid marbles, which limits their application as miniature reactors for long-term chemical reactions. In this study, to prevent volatilization and maintain long-term stability, stable liquid marbles were fabricated by encapsulating glycerol/water droplets using superhydrophobic cellulose nanocrystals. The influence of water evaporation and absorption on the stability of aqueous glycerol marbles at different relative humidities (RHs) was investigated. At the same RH, the evaporation/absorption rates of the liquid marbles decreased on increasing the glycerol concentration. For the liquid marbles with the same glycerol volume concentration, the evaporation rates decreased with the increase in RH. The liquid marbles exhibited higher evaporation/absorption resistance compared with pure naked liquid droplets.